Sistem Keamanan Lingkungan Berbasis IoT dan Mobile App - Frendiana, Viving; Dandun Widhiantoro; Budi Utami; Shita Herfiah; Annisa Octaviani Purwaningtyas; Fachma Oktafiani (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to implement an Internet of Things (IoT)-based environmental security system integrated with mobile applications to improve the quality of life of residents in RT 01 RW 03 Beji Timur. The main problems identified include high crime rates and inefficient manual administrative systems. Using the Participatory Action Research (PAR) approach, the system was developed with hardware components consisting of ESP32 microcontroller, DFPlayer Mini module, and PAM8610 amplifier connected through Firebase Realtime Database. The E-RT 01 RW 03 mobile application provides alarm alert feature with queue logic, transparent bookkeeping, digital dues cards, and electronic letter submission. The evaluation results show a significant increase in participants' knowledge from an average score of 74 to 81 after training. Although there was a slight decrease in usage intention (78 to 77) and training evaluation (78 to 76), these values still indicate positive community response. The system successfully provides fast emergency response, administrative transparency, and easy-to-use interface.